Modern UX research as an empirical basis for the applied sociological theory of the culture of digital behaviour - A. S. Vydrina (Цифровая социология)
The article is devoted to the consideration of methods for studying the phenomenon of modern digital culture – user experience (hereinafter referred to as UX). This phenomenon includes knowledge and skills, as well as the results of human behaviour as a user of digital resources (products, systems). UX research is aimed at studying and analysing the processes of direct human contact with various online products: websites, applications and many others. The article provides an overview of automated desk methods, methods for selecting methods in empirical research, then methods for collecting (traditional and UX-specific) and processing data. Analysis of them shows that the cornerstone issue of systematisation of methods is the search for balance in such dichotomous complexes as “usability – hedonism”, “offline – online”; it is in these complexes that the most interesting and specific processes of mixing methods, standardisation of methods and the emergence of new concepts in the field of culture take place digital behaviour. Together with this, the author analyses the possible future transformation of UX research methodology into an applied industry theory of digital culture within the framework of sociological knowledge. The author comes to the conclusion that the results of this transformation will probably be noticeable no earlier than in 10 years, provided that digitalisation does not change its vector. However, the author believes, it is now necessary to observe the process of formation of this branch of sociological knowledge, because UX research practitioners constantly present repeated results of measurements of various aspects of people’s digital behaviour. Methodologists of sociological knowledge study the adaptation of classical sociological methodology to digital culture, as well as to the life of society at the intersection of offline and online.